EXPERT FUZZY SYSTEMS FOR EVALUATION OF INTENSITY OF REACTIVE EDEMA OF SOFT TISSUES IN PATIENTS WITH DIABETES - Shkilniak, Liudmyla; Wójcik, Waldemar; Pavlov, Sergii; Vlasenko, Oleg; Kanishyna, Tetiana; Khomyuk, Irina; Bezverkhyi, Oleh; Dembitska, Sofia; Mamyrbayev, Orken; Iskakova, Aigul (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The paper analyzes the main areas of application of mathematical methods in medical diagnostics, formulates principles of diagnostics based on fuzzy logic; developed mathematical models and algorithms that formalize the process of making diagnostic decisions based on fuzzy logic with quantitative and qualitative parameters of the patient’s condition; developed mathematical models of membership function. Mathematical models and algorithms have been developed that formalize the process of making diagnostic decisions based on fuzzy logic with quantitative and qualitative parameters of the patient’s condition; developed mathematical models of membership functions, formalizing the representation of quantitative and qualitative parameters of the patient’s condition in the form of fuzzy sets, used in models and algorithms for diagnosis and finding a diagnosis of assessing the intensity of reactive postoperative edema in patients of all study groups. An expert system was implemented for solving the problems of medical diagnosis based on fuzzy logic when assessing the intensity of reactive swelling of soft tissues, which develops in the postoperative period in patients of all study groups against the background of diabetes. The paper analyzes the main areas of application of mathematical methods in medical diagnostics, formulates the principles of diagnostics based on fuzzy logic.